Organoleptic and Proximate Analysis of Natto (Yellow Soy Fermented Food by The Bacterium Bacillus subtilis natto) - Sahirman Sahirman (Universitas Djuanda, 2021)
This research aims to conduct organoleptic and proximate analysis of yellow soybean natto which is a food fermented from soybeans by Basillus subtillus natto. Natto is a traditional food originating from Japan that is classified as a probiotic food because it is consumed in fresh condition with the bacteria Basillus subtillus natto in it. Organoleptic analysis of natto in this study consisted of tests of texture, taste, color and aroma, while proximate analysis consisted of analysis of water content, protein content, fat content, carbohydrate content, and ash content. The results of the yellow soybean natto analysis show that the natto originating from Vedca Cianjur has a slimy sticky texture, brown color, a slightly sour and musty aroma like semangit tempeh and the savory taste of soybeans which is the distinctive aroma of natto. Proximate analysis shows that natto contains an average water level of 58.4± 0.50 %wb, average protein content of 20,1 ± 0.65 %wb, average fat content of 9.4 ± 0.42% wb, average carbohydrate content of 7.6 ± 0.47% wb, and the average ash content of 2.3 ± 0.19% wb. Keywords: physical, proximate, natto, Basillus subtillus natto